SGLT2 inhibitor improves the prognosis of patients with coronary heart disease and prevents in-stent restenosis - Zhang, Qing; Deng, Zhiwen; Li, Tudi; Chen, Kaitong; Zeng, Zhihuan (Frontiers in Cardiovascular Medicine, 2024)
Coronary heart disease is a narrowing or obstruction of the vascular cavity caused by atherosclerosis of the coronary arteries, which leads to myocardial ischemia and hypoxia. At present, percutaneous coronary intervention (PCI) is an effective treatment for coronary atherosclerotic heart disease. Restenosis is the main limiting factor of the long-term success of PCI, and it is also a difficult problem in the field of intervention. Sodiumglucose cotransporter 2 (SGLT2) inhibitor is a new oral glucose-lowering agent used in the treatment of diabetes in recent years. Recent studies have shown that SGLT2 inhibitors can effectively improve the prognosis of patients after PCI and reduce the occurrence of restenosis. This review provides an overview of the clinical studies and mechanisms of SGLT2 inhibitors in the prevention of restenosis, providing a new option for improving the clinical prognosis of patients after PCI.